The Effects of Land Uses on Soil Physical Health in Agricultural Land (Case Study: Kismantoro District, Central Java Province, Indonesia) - Mujiyo; Sari, Sandrina; Ariyanto, Dwi Priyo; Cahyono , Ongko (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2025)
Kismantoro district is a karst land with unique characteristics and its physical health is easily influenced by land use. The purpose of this study was to identify the physical health status of soil, and find the influence of land use and parameters that limit soil physical health, which eventually provide appropriate land management strategies and recommendations to improve soil health. The research was conducted using a descriptive explorative approach and a purposive sampling method on the 12 Land Map Units (LMU) with three replications. Data were analysed using Analysis of Variance and Pearson correlation. Results indicated that most soil physical health in agricultural land in Kismantoro District is healthy. The highest soil physical health status was found on plantation agricultural land, with the average of the soil physical health being high status of 63.22%, followed by moor agricultural land at 52.83% and rice fields at 48.2%. The determinant factors of soil physical health were soil porosity, bulk density, and soil texture. To enhance the physical health of agricultural soil in Kismantoro District, it is recommended to apply organic matter, adopt zero or no-tillage practices, and grow cover crops on agricultural land. Keywords: determinant factor, soil compaction, soil texture, sustainable management